Strategy for developing of small medium industry to creative industry in special culinary, Sarolangun Regency - Fitriaty Fitriaty; Dwi Kurniawan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study aims to obtain a description of small and medium industries in the area of regional culinary Sarolangun, internal and external factors and formulate strategies to develop the industry to become a creative industry. The method that is used SWOT analysis, descriptive and qualitative analysis. Based on the research result found that the culinary that can be developed is coconut bread, dodol, kipang cake and curry fish curry fish. The weakness of internal factors lies in working capital, human resources, and external factors lie in marketing and institutional. The recommended strategy is to turn around. Keywords: SME’s, Culinary, SWOT Analysis, Turn around